Introduction to linear algebra - Tay, Choo Chuan (Penerbit Universiti Teknikal Malaysia Melaka, 2010)
This book is designed to familiarize the student with the form of questions asked in Linear Algebra. An excellent student must have an initiative to learn before being taught by lecturers. By using this book, students can be more prepared before attending a tutorial session. The examples are presented in a sequence of steps with full details so that students can follow systematically.